The use of bone block allografts in sinus augmentation, followed by delayed implant placement: A case series - Eurico D Aloja; Massimiliano Ricci; Guerino Caso; Enrico Santi; Tonelli Paolo; Barone Antono; Ugo Covani (Wolters Kluwer Medknow Publications, 2013)
Purpose: This article reports the clinical outcomes observed in a large number of patients receiving block bone allograft used for sinus augmentation and delayed implant placement. Patients and Methods: In total, 28 patients (13 males) with a mean age of 49.8 ± 10.1 years (range: 33-67 years) were included in this case series. All selected patients suffered from severe alveolar ridge atrophy in the posterior maxilla and required bone augmentation procedures, followed by implant placement after 6 months. All patients were followed for 18 months after the grafting, with scheduled monthly visits and/or more frequent visits if required. The survival rates for both the bone blocks and placed implants were then evaluated. Results: A total of 42 blocks and 90 implants were placed. Only one bone graft and 5 implants failed; the survival rate was 97.2% and 95.5% for the bone grafts and implants, respectively. The graft failed due to the onset of post-surgical infectious sinusitis, while in some patients' implants showed absence of osteointegration at the end of the healing phase. Of note, all failed implants were observed in heavy smokers; in all other patients, blocks and implants were successful. Conclusions: This preliminary case series suggests that the grafting of bone allograft followed by delayed implant placement may be a promising strategy for sinus augmentation. More extended and larger follow-up studies are needed to confirm this preliminary data.